Higher Education Internationalization and English Language Practices: Academics Perspectives - Puspita, Indah Triyana; Silvhiany, Sary; Petrus, Ismail (Edukasi, 2025)
The process and outcomes of higher education's internationalization have been enhanced in this internet era as the world becomes increasingly connected. The phenomenon of “internationalization of higher education” has emerged over the past 30 years, including in Indonesia. Internationalization refers to the integration of an international perspective into a university or college’s teaching and learning, research, services, and overall operations. This study was conducted at Sriwijaya University and aimed to explore English language practices within the institution, as well as the perspectives of study program coordinators and lecturers regarding the internationalization of higher education. A qualitative method was employed to gather data through semi-structured interviews, and the data were analyzed using thematic analysis. The results showed that English is a vital component of instruction, communication, and institutional development, playing a significant role in promoting the internationalization process. Moreover, the findings indicated that language barriers remain a major obstacle to the globalization of higher education, particularly in integrating international students into classroom environments. However, consistent exposure to English through classes, conversations, and institutional programs, such as international seminars and bilingual academic events, significantly improves students' language engagement and proficiency.